1997
DOI: 10.1136/jech.51.3.272
|View full text |Cite
|
Sign up to set email alerts
|

Political changes and trends in cardiovascular risk factors in the Czech Republic, 1985-92.

Abstract: Background-Mortality from cardiovascular diseases is substantially higher in central and eastern Europe than in the west. After the fall of communism, these countries have undergone radical changes in their political, social, and economic environments but little is known about the impact of these changes on health behaviours or risk factors. Data from the Czech Republic, a country whose mortality rates from cardiovascular diseases are among the highest, were analysed in this report. Objectives-To examine the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 11 publications
2
26
0
Order By: Relevance
“…A similar development of the health situation was observed in this period in the Czech Republic and Slovakia [23,24]. The main reason for the decline in adult premature mortality in these countries was also the rapid decrease of cardiovascular disease mortality.…”
Section: Health Improvement After 1991supporting
confidence: 74%
“…A similar development of the health situation was observed in this period in the Czech Republic and Slovakia [23,24]. The main reason for the decline in adult premature mortality in these countries was also the rapid decrease of cardiovascular disease mortality.…”
Section: Health Improvement After 1991supporting
confidence: 74%
“…Also, although the Eastern European countries that participated in OPUS-TIMI 16 have experienced different socioeconomic environments and trends in coronary mortality during the 1990s, the small number of patients enrolled in each country did not permit intra-region analysis [4,22,23].…”
Section: Limitationsmentioning
confidence: 99%
“…In Poland, CHD mortality approximately doubled from 1970 to 1991 (135). But starting in 1992, CHD mortality decreased rapidly during a time of swift political and economic changes, and an examination of the potential factors that could have contributed to this reduction concluded that dietary changes best explained this reduction (11). Subsidies for dairy and animal fats decreased and consumption of vegetable oils rose rapidly, transforming the polyunsaturated/saturated fatty acid ratio (136).…”
Section: Natural Experimentsmentioning
confidence: 99%
“…The "natural experiments" of Cuba and several countries in Central and Eastern Europe provide fascinating insights into the modifiable and dynamic nature of CHD mortality (11,53,135). During the 1990s, Cuba experienced its "special period" after losing the Soviet Union as a trading partner.…”
Section: Natural Experimentsmentioning
confidence: 99%